Translational Research in Cancer Drug Development - Meiyanto, Edy; Hermawan, Adam; Anindyajati, . (Indonesian Journal of Cancer Chemoprevention, 2011)
The development of cancer treatment were initiated by the existence of humanÃ¢â¬â¢s effort to treat by applying certain materials which is mostly part(s) or extracts of plants, which are now adapted as traditional herbal medicine. The discovery of new drugs was based on intuition and empirical evidence. Thus, high luck factor was involved in a successful treatment with unguaranteed reproducibility. One example of drug being developed through conventional drug development is Taxol. Taxol is an extremely complex natural product and requires a bunch of hard work with high level of serendipity to be discovered as antitumor agent. Recently, rapid development in human biology and technology allow a change in drug discovery strategy by minimizing the luck factor. Targeted therapy has been a very promising strategy of drug development research, especially in cancer treatment. Although cancer has been known as a disease with very complex cellular and histo-pathophysiology, the abundance of studies on proteins, such as receptors and hormones, as the hallmarks of cancer allows us to explore carcinogenesis suppression further based on molecular targeted therapy. Kinases, one type of protein involved in signal transduction regulating cell growth and differentiation, could be the proteins thatÃÂ  are proposed to be inhibited in suppressing tumor growth. An interesting example of the drug being discovered based on molecular modeling is the discovery of lapatinib as anti-cancer with specific target on HER-2 and EGFR to overcome the resistance of cancerÃÂ  to Herceptin caused by elevated level of EGFR expression.